A MDM2‐dependent positive‐feedback loop is involved in inhibition of miR‐375 and miR‐106b induced by Helicobacter pylori lipopolysaccharide. Issue 9 (28th October 2014) - Ye, Feng; Tang, Chunli; Shi, Weijia; Qian, Juan; Xiao, Shuping; Gu, Min; Dang, Yini; Liu, Jianping; Chen, Yan; Shi, Ruihua; Zhang, Guoxin
<x xml:space="preserve">Abstract</x> Dysregulation of microRNAs (miRNAs) has been linked to virulence factors of Helicobacter pylori and shown to contribute to the progression of gastric cancer. However, the mechanisms of these processes remain poorly understood. The aim of this study was to investigate the mechanisms by which lipopolysaccharide (LPS), a virulence factor of H. pylori, regulates miR‐375 and miR‐106b expression in gastric epithelial cells. The results show that LPS from H. pylori 26695 downregulated the expression of miR‐375 and miR‐106b in gastric epithelial cells, and low levels of Dicer were also observed. Downregulation of miR‐375 was found to increase expression of MDM2 with SP1 activation. Overexpression of MDM2 inhibited Dicer by repressing p63 to create a positive‐feedback loop involving SP1/MDM2/p63/Dicer that leads to inhibition of miR‐375 and miR‐106b expression. In addition, we demonstrated that JAK1 and STAT3 were downstream target genes of miR‐106b. H. pylori LPS also enhanced the tyrosine phosphorylation of JAK1, JAK2 and STAT3. Together, these results provide insight into the regulatory mechanisms of MDM2 on H. pylori LPS‐induced specific miRNAs, and furthermore, suggest that gastric epithelial cells treated with H. pylori LPS may be susceptible to JAK/STAT3 signal pathway activation via inhibition of miR‐375 and miR‐106b.